TINGKAT PENGETAHUAN DAN TINGKAT STRES DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI DESA MAYUNGAN II KALURAHAN MURTIGADING SANDEN BANTUL - Parmadi Sigit Purnomo; Norra Hendarni Wijaya (CV. Denasya Smart Publisher, 2026)
Hypertension or high blood pressure is a chronic medical condition characterized by a persistent increase in blood pressure above the normal threshold. Systolic blood pressure is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. This study aims to determine the relationship between knowledge levels and stress levels with the incidence of hypertension in the elderly. This type of research is quantitative using a case-control approach used to assess the role of risk factors for the disease. The population of this study were hypertension cases 50-89 years old, obtained from the latest data from hypertension classes in October 2025 in Mayungan II Village, Murtigading Village, Sanden, Bantul, with a total of 22 people. Using a total sampling of 22 case groups and 22 control groups with a total of 44 respondents. The results of the chi-square test show a Continuity Correction value of 7.425 with an Asymp.Sig.(2-sided) value of 0.006, meaning that the value is smaller than (α = 0.05) so that it can be stated (0.006 <0.05). and x² count 7.425> x² table 3.841) with Df = 1, it can be concluded that Ha is accepted and Ho is rejected, which means there is a significant relationship between knowledge and the incidence of hypertension in the elderly with an Odds Ratio (OR) for the knowledge variable (Not good/good) which is 7.286 (95% CI, 1.905–27.861). This shows that elderly people with a poor level of knowledge have a risk of experiencing hypertension 7.286 times greater than elderly people who have a good level of knowledge. The results of the Chi-Square test show a significant value (a = 0.000) and df = 2, where the value <0.000 and x² count (17,468) ≥ x² table (5,991), then Ha is accepted Ho is rejected. In conclusion, there is a relationship between the level of knowledge and stress levels with the incidence of hypertension in the elderly in Mayungan II Village, Murtigading Sanden Village, Bantul.